Global patterns of terrestriality in amphibian reproduction. Issue 6 (28th January 2019) - Lion, Marília Bruzzi; Mazzochini, Guilherme Gerhardt; Garda, Adrian Antonio; Lee, Tien Ming; Bickford, David; Costa, Gabriel Correa; Fonseca, Carlos Roberto
Abstract: Aim: Amphibians exhibit two basic reproductive modes, terrestrial and aquatic, each with different ecophysiological constraints related to evaporative water loss. We hypothesize that these fundamental niche differences will generate strong geographical patterns at the global scale in response to spatial heterogeneity in temperature and water availability. Location: Global. Time period: Present. Major taxa studied: Amphibians. Methods: We used global distribution maps of 5, 434 amphibian species, classified into terrestrial or aquatic breeders, to estimate the occurrence and proportion of terrestrial breeding species per 1° cell. We used multiple regression models to test the relative importance of seven abiotic variables: annual precipitation, annual mean temperature, annual mean relative air humidity, annual mean actual evapotranspiration, availability of lotic and lentic environments and slope. We used residuals autocovariate (RAC) generalized multiple regression models to control for spatial autocorrelation and a spatial vector based on amphibian phylogeny to account for phylogenetic dependencies among cells. Model generality was evaluated by contrasting results between 11 widely recognized world zoogeographical realms. Results: Globally, the occurrence of terrestrial breeding species was better explained by temperature followed by total annual rainfall, relative air humidity and terrain slope. In contrast, the proportion of terrestrial breeders was better explained by terrain slope, followed by total rainfall, temperature and relative air humidity. Actual evapotranspiration and the extension of large lotic and lentic water bodies played a minor role. However, the relative importance and even the sign of the regression coefficients varied among realms, revealing different evolutionary pressures. Main conclusions: Niche differences among terrestrial and aquatic breeding amphibian species are reflected in their distinct geographical distribution across the globe. Adequate conditions for terrestrial reproduction to evolve and thrive are reached in distinct ways in different realms. Temperature constraints and slope suggest that reproductive modes will be impacted differently by climate change.